Development and prospective validation of a risk score model in guiding individualized concurrent chemoradiotherapy in stage II nasopharyngeal carcinoma in intensity‐modulated radiotherapy era - Yang, Shan‐Shan; Pang, Ya‐Jun; Wang, Zhi‐Qiang; Zhang, Bao‐Yu; Liu, Zhi‐Qiao; Chen, En‐Ni; OuYang, Pu‐Yun; Xie, Fang‐Yun (Cancer medicine (Malden, MA), 2022)
Purpose We aimed to develop and prospectively validate a risk score model to guide individualized concurrent chemoradiotherapy (CCRT) for patients with stage II nasopharyngeal carcinoma (NPC) in intensity‐modulated radiotherapy (IMRT) era. Materials and Methods In total, 1220 patients who received CCRT or IMRT alone were enrolled in this study, including a training cohort (n = 719), a validation cohort (n = 307), and a prospective test cohort (n = 194). Patients were stratified into different risk groups by a risk score model based on independent prognostic factors, which were developed in the training cohort. Survival rates were compared by the log‐rank test. The validation and prospective test cohorts were used for validation. Results Total tumor volume, Epstein–Barr virus DNA, and lactate dehydrogenase were independent risk factors for failure‐free survival (FFS, all p < 0.05). A risk score model based on these three risk factors was developed to classify patients into low‐risk group (no risk factor, n = 337) and high‐risk group (one or more factors, n = 382) in the training cohort. In the high‐risk group, CCRT had better survival rates than IMRT alone (5‐year FFS: 82.6% vs. 74.0%, p = 0.028). However, there was no survival difference between CCRT and IMRT alone either in the whole training cohort (p = 0.15) or in the low‐risk group (p = 0.15). The results were verified in the validation and prospective test cohorts. Conclusion A risk score model was developed and prospectively validated to precisely select high‐risk stage II NPC patients who can benefit from CCRT, and thus guided individualized treatment in IMRT era. Stage II nasopharyngeal carcinoma patients cannot benefit from concurrent chemoradiotherapy. A risk score model were developed and prospectively validated to precisely select high‐risk patients who can gain survival benefit from concurrent chemoradiotherapy, and thus guide individualized treatment in stage II nasopharyngeal carcinoma.